Penegakan Peraturan Daerah Kabupaten Kampar No. 9 Tahun 2008 Tentang Pengolahan Pertambangan Umum - Masri Masri; Ardiansah -; Bagio Kadaryanto (jurnal.unprimdn.ac.id, 2020)
The existence of Kampar Regency Regional Regulation No. 09 of 2008 concerning General Mining Management demonstrates the local government's desire to improve people's lives while also preserving the environment. However, there are still issues with implementing this regional rule, such as the fact that there are still miners from the neighboring community who do not have licences to carry out the present mining activities. The goal of this study was to see how the Kampar Regency Regulation No. 9 of 2008 on General Mining Processing was implemented, particularly in the categorization of excavated mining material type c. The Civil Service Police Unit of Kampar Regency was used as the research venue for sociological legal research. Primary, secondary, and tertiary data were used, and 9 persons were allocated to responders who clearly understood the situation. The authors utilize observation, structured interview and documentation study. Data analysis was carried out using qualitative legal methods, which entails describing and describing the data obtained based on supporting theories in order to be able to make a conclusion that ranges from broad to particular. According to the findings of the study, quarry miners in Kampar Regency were subjected to both preventive and repressive law enforcement in order to comply with regional laws. The presence of traditional miners in the local community, who are hereditary, is an impediment. The lack of public knowledge and government socialization has resulted in a lack of enforcement of these regional rules.